Mobile app to promote environmental awareness - Shen, Yuxuan (Nanyang Technological University, 2024)
As global industrialization progresses, the quality of human life's environment is steadily declining. Despite numerous reports and articles highlighting environmental degradation from various countries and institutions, they often fail to garner as much attention as mainstream entertainment news. The author posits that this discrepancy arises from the absence of a cohesive platform for environmental news and articles, such as a mobile application enabling users to access and learn about environmental issues conveniently and on-the-go. Henceforth, the author has created a mobile application named 'OurEarth' aimed at fostering environmental awareness among users. This software will furnish users with information on environmental degradation, conservation efforts, offline environmental activities, and more.